2012
DOI: 10.1176/appi.ajp.2012.12010073
|View full text |Cite
|
Sign up to set email alerts
|

Presupplementary Motor Area Hyperactivity During Response Inhibition: A Candidate Endophenotype of Obsessive-Compulsive Disorder

Abstract: These findings suggest that presupplementary motor area hyperactivity is a neurocognitive endophenotype of OCD that is possibly related to inefficient neural processing within the presupplementary motor area itself. Patients with OCD further showed a state-dependent deficit in recruiting right inferior parietal cortex and inferior frontal gyrus, which may contribute to their inhibition deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
191
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 268 publications
(224 citation statements)
references
References 42 publications
24
191
9
Order By: Relevance
“…Furthermore, D'Urso et al [94] reported, in a randomized cross-over trial of anodal vs cathodal tDCS to the pre-SMA, that the cathodal application was significantly superior to anodal tDCS in reducing OCD symptoms. The results of this study are in line with findings of clinical efficacy of inhibitory rTMS to pre-SMA [95] , demonstrated to be hyperactive in OCD patients during performance of cognitive tasks related to attentional aspects of action control [96,97] . The evidence deriving from the clinical efficacy of inhibitory rTMS and tDCS and from neurophysiological measures of altered motor cortex excitability in OCD [91] , that normalized after 1-Hz rTMS to the pre-SMA [98] , suggests that the pre-motor/motor system is abnormally hyperactive in OCD, and that there is a pathophysiological link between such hyperexcitability and OCD symptoms.…”
Section: Obsessive-compulsive Disordersupporting
confidence: 88%
“…Furthermore, D'Urso et al [94] reported, in a randomized cross-over trial of anodal vs cathodal tDCS to the pre-SMA, that the cathodal application was significantly superior to anodal tDCS in reducing OCD symptoms. The results of this study are in line with findings of clinical efficacy of inhibitory rTMS to pre-SMA [95] , demonstrated to be hyperactive in OCD patients during performance of cognitive tasks related to attentional aspects of action control [96,97] . The evidence deriving from the clinical efficacy of inhibitory rTMS and tDCS and from neurophysiological measures of altered motor cortex excitability in OCD [91] , that normalized after 1-Hz rTMS to the pre-SMA [98] , suggests that the pre-motor/motor system is abnormally hyperactive in OCD, and that there is a pathophysiological link between such hyperexcitability and OCD symptoms.…”
Section: Obsessive-compulsive Disordersupporting
confidence: 88%
“…Although not an a priori ROI, we observed parietal hypoactivity during fear regulation in patients as well. In the context of the wider OCD literature (Menzies et al 2008;de Wit et al 2012), our data suggest that impaired cognitive control in OCD is related not only to dysfunction of the dorsal PFC but to a wider distributed frontal-parietal network.…”
Section: Emotion Regulationmentioning
confidence: 65%
“…In healthy individuals, the VRP and the IFG/ operculum have been shown to be functionally (restingstate fMRI) and structurally (diffusion tensor imaging) con nected, 30,38,39 and significant structural covariance between them has also been reported. 13 Results in OCD samples have shown abnormal taskrelated activity in both regions [40][41][42] as well as changes in functional connectivity between them. 21 Re garding morphometric assessments, different studies have de tected cortical thickness 43 and grey matter volume reductions in the IFG/frontal operculum region 34,44,45 as well as volume enlargements in the ventral putamen.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, recent research has shown how these re gions show aberrant activity in patients with OCD during tasks of cognitive control and conflict processing. 41,42 Interestingly, the IFG/frontal operculum activity seems to specifically regulate behaviour in lowpredictability scenarios, thus allowing for fast and accurate responding in changing environments, 48 a pattern of response that is opposite to compulsive behaviour and clearly disrupted in patients with OCD.…”
Section: Discussionmentioning
confidence: 99%